Public Awareness Towards Value Added Tax (VAT) System in Hetauda Sub-metropolitan City Area - Sapkota, Tika Prasad (Journal of Business and Social Sciences, 2021)
Value added tax (VAT) is indirect sources of revenue collection of nation. It has been the most essential choice like our developing countries, Nepal. Which leads to revenue enhancement and sustainable economic development. As VAT was an emerging concept in Nepal, a comprehensive taxpayer education program was launched to impart knowledge regarding the various aspects of VAT to parliamentarians, industrialists, businessmen, consumers as well related society. The study used descriptive and survey research design. Data were collected through questionnaires. Statistical tools were used to make a proper analysis. It is found that 20% businessmen and 33.33% consumers are not aware that the Government of Nepal is levying VAT on all kind of products, 36% consumers are not aware of the fact that you pay VAT whenever you purchase any product, 88 % of the total respondents knowledge on earning from VAT is a major source of revenue for Government, only 44 % response of respondents are in favor of billing system, 33.33% consumer are not aware about existing rate of VAT in Nepal, 44% consumers specify the other problem in the present VAT implementation except VAT collection ,VAT refund and registration. Most of them ask for tax invoice to get the authenticity of sellers. VAT must be successful and this largely depends upon the public awareness, honesty, faith and morality of tax officials and the business community. There is a need for willpower and action. It is also found that public awareness program and tax education play prime role to increase the VAT revenue in Nepal. The finding of this study is majority of Tax expert and businessmen are aware about VAT system but the training and awareness program is essential.